The Potential of Banyubiru Natural Sites as Local History Content in History Learning - Fitriyah, Lailatul (Swarnadwipa, 2025)
The Banyubiru Natural Site is a tourist spot that has the potential to be used as a sources of historical learning. As a tourist spot, this place holds historical relics which are very important to be integrated into history learning in schools. The reasearcher considers that writing this research is important with the aim of knowing the potential of the Banyubiru Natural Site as local historical content in history learning. This research uses historical methods with four stages of vastu heuristics, verification, interpretation and historiography. The results of the research show that local history plays an important role so that students can to properly appreciate the development of their society in the past up to the present that occurred in their own environment. The Banyubiru Natural Site as local historical content is really needed to be integrated in learning because the site is in accordance with the scope of material in history learning which has been determined in the independent curriculum, namely in phase E class X which is related to material on “The Entry of Hindu-Buddhist Religion and Culture in Indonesia”.